Folkehøjskolerne og folket. Roar Skovmand: Folkehøjskolen i Danmark 1841-1892 - Skrubbeltrang, Fridlev (Grundtvig-studier, 1948)
Review of Roar Skovmand’s ” Folkehøjskolen i Danmark, 1841— 1892“. By Fridlev Skrubbeltrang. Skovmand claims that the development of the Danish people in the second half of the 19th century can only be understood in connection with the Folk High-School movement. This is true, but only if we are speaking of rural, peasant Denmark, for it is not until the 20th century that the Folk High-Schools gained any considerable ground in the towns and among the workers. Historically there is nothing surprising in this development. The idea of educating the country youth sprang from the fruitful soil of the great land reforms ; and Grundtvig as a young man dreamt of “ sacrificing everything for the enlightenment of the peasants” . But in the 1840’s it was chiefly R. Sørensen’s plans for agricultural schools for the peasants that were being discussed, and only after 1864 did it become clear that it was Grundtvig’s Folk High-School idea that would triumph. Most of those who have previously written the history of the High-Schools have done so on the basis of their own personal experiences in the High-School movement. Skovmand has done it from a more scientific standpoint. He is less interested in the Folk High-School idea than in the way in which ideas and plans were carried into effect, and modified in the light of practical realities. He gives full place to the influence of the leading High-School personalities, and much of his book is based on their private papers, to which he has had access, as well as on the records of government departments. We learn much about the work of the High-Schools and its guiding tendencies, but comparatively little about its effect upon the students. The High-School’s fruits cannot be weighed or measured; but it opened new horizons and new worlds of thought and feeling to the young people of the country districts. From the rationalist point of view it was criticised as too fantastically idealistic, and likely to pervert the sound practical sense of the peasants. But the history of the rise of the Danish co-operative movement proved that the former students of the High- Schools by no means lacked realism and practical sense, and the High-Schools reaped much of the credit for its material success. Jakob Knudsen, friend and most exacting critic of the Folk High-School, demanded that it should be truly “ folkelig” and should develop the best characteristics of the peasants themselves, at a time when they were taking an increasingly prominent part in public life. But most of the leading High-School teachers came from other social classes; and it was hard for them to develop a genuine “ peasant culture” . The High-Schools gave many of their students a new joy in life, and a new desire to achieve something of value in co-operation with their fellows; but in some cases the enthusiasm they aroused was only transitory. It is not easy to measure the influence of the Folk High-School apart from that of the revival in the Church, with which it was closely connected. Many clergymen and teachers in children’s schools throughout the country shared with the High-School teachers in the work of enlightenment. Skovmand obviously knows the High-School from within, but he is less familiar with the life of the peasants in general. Much of the material which Skovmand uses to illustrate the attitude of the Government and Parliament to the High-Schoools is new, and throws fresh light on the position of the High-Schools in the political life of the country and on government policy with regard to grants, inspection, etc. Skovmand describes the attitude of the High-School to contemporary tendencies of thought (religious, political and national) as being “ as open as it could be if it were not to be wholly carried away by them” . In another little book (“Højskolen gennem 100 Aar” ) Skovmand brings the history of the High-School up to date. Denmark might have had good “ higher schools for peasants” and a co-operative movement even if Grundtvig had never lived, but there is no doubt that from him came the central driving force of the Folk High-School movement, which has won world fame. Skovmand strongly opposes Vilhelm la Cour’s suggestion that in the period after 1870 the High-School movement abandoned many of its original ideas, and lost much of its power. “ The power was not lost, but had found a broader channel”, is his verdict. His book is the product of conscientious research combined with a real love for his subject.